2017
DOI: 10.1177/1934578x1701200910
|View full text |Cite
|
Sign up to set email alerts
|

Chelidonine and Homochelidonine Induce Cell Death through Cell Cycle Checkpoints and MAP Kinase Pathways

Abstract: This study focuses on the comparative in vitro cytotoxicity of chelidonine and homochelidonine on human cancer and non-cancer cells. Both alkaloids produced a decrease in cellular growth in a dose-dependent manner exhibiting greater potency in cancer cells. The growth inhibitory effect was evidenced in both ovarian carcinoma A2780 and lung fibroblast MRC-5 cells by inducing G2 and mitotic phase cell cycle arrest. Results indicated that the extent of apoptosis induced by chelidonine and homochelidonine was corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 32 publications
(19 reference statements)
0
8
0
Order By: Relevance
“…Nonetheless, existing clinical evidence is not sufficient to recommend extracts of the herb for usage (European Medicines Agency, 2011) [19]. In previous studies on its mechanisms of action, chelidonine was found to present with cytostatic activity, whereas berberine (16), chelerythrine, and sanguinarine presented with DNA-intercalating abilities, thereby interfering with cell division and replication [10,11,13,14,20]. It is worth noting that the application of Chelidonium-derived products in the treatment of cancer has also been suggested [21].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nonetheless, existing clinical evidence is not sufficient to recommend extracts of the herb for usage (European Medicines Agency, 2011) [19]. In previous studies on its mechanisms of action, chelidonine was found to present with cytostatic activity, whereas berberine (16), chelerythrine, and sanguinarine presented with DNA-intercalating abilities, thereby interfering with cell division and replication [10,11,13,14,20]. It is worth noting that the application of Chelidonium-derived products in the treatment of cancer has also been suggested [21].…”
Section: Discussionmentioning
confidence: 99%
“…Derivatives of protopine, chelidonine, coptisine, and berberine were also present, but in amounts below LOQ (Table 1). Three nonaromatic carboxylic acids (malic acid (1, dicarboxylic acid), trans-aconitic acid (2, polycarboxylic acid), and quinic acid (3, cyclohexanecarboxylic acid)); three hydroxybenzoic acids (salicylic acid (7), protocatechuic acid (4), and vanillic acid (5)); two hydroxycinnamic acids (trans-caffeic acid (6) and p-coumaric acid (9)); one caffeic acid ester (rosmarinic acid (10)); one flavonoid (quercetin (17)); one phenolic aldehyde (vanillin (11)); and one quinine sulfate (14) were detected in the root extract.…”
Section: Phytochemical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…However, other mechanisms have been also discovered, albeit most studies used in vitro experiments on cell lines. Chelidonine [1] appeared to exert its cytostatic activity through interactions with microtubules and thereby causing cell cycle arrest (Panzer et al, 2001 ; Havelek et al, 2016a ).…”
Section: Pharmacological Activities and Clinical Evidencementioning
confidence: 99%
“…Crude extracts of CM, as well as purified compounds derived from it, exhibit a broad spectrum of bioactive properties with a potential for the protection of human health, such as antiinflammatory, antimicrobial, cytotoxic, analgesic, antioxidant, antiulcer, acetylcholinesterase-and butyrylcholinesterase-inhibitory, and hepatoprotective activities (Lee et al, 2007;Kuenzel et al, 2013). The high spectrum of antioxidant properties for CM that are increasingly being used suggests the necessity of further investigations regarding their influence on organs and tissue function, including the evaluation of molecular mechanisms involved to exploit them for potential therapeutic benefits (Lenfeld et al, 1981;Kokoska et al, 2002;Havelek et al, 2016).…”
Section: Introductionmentioning
confidence: 99%